2020
DOI: 10.1080/07391102.2020.1837679
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites from spice and herbs as potential multitarget inhibitors of SARS-CoV-2 proteins

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been responsible for the current global pandemic that has caused a death toll of >1.12 million worldwide and number continues to climb in several countries. Currently, there are neither specific antiviral drugs nor vaccines for the treatment and prevention of COVID-19. We screened in silico , a group of natural spice and herbal secondary metabolites (SMs) for their inhibition efficacy against multiple target proteins of SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 67 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…In recent times, researchers are working to find out some potential lead compounds from medicinal plants that are active against several enzymes and other proteins responsible for viral replication and growth (Gupta et al, 2020b;Krupanidhi et al, 2020;Pendyala and Patras, 2020 ). Several studies reported the inhibitory potential of several herb derived phytochemicals against SARS-CoV-2 (Dhama et al, 2018;Gupta et al, 2020b;Jalali et al, 2020). The advancement of numerous computational technology has affected vastly in biology and computational biology, incorporating both computational algorithms and biological data, which has emerged as a breakthrough in modern drug discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, researchers are working to find out some potential lead compounds from medicinal plants that are active against several enzymes and other proteins responsible for viral replication and growth (Gupta et al, 2020b;Krupanidhi et al, 2020;Pendyala and Patras, 2020 ). Several studies reported the inhibitory potential of several herb derived phytochemicals against SARS-CoV-2 (Dhama et al, 2018;Gupta et al, 2020b;Jalali et al, 2020). The advancement of numerous computational technology has affected vastly in biology and computational biology, incorporating both computational algorithms and biological data, which has emerged as a breakthrough in modern drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, with the help of the GC-MS technique, seventy-four compounds had been isolated, among which thirty bioactive compounds were enlisted and subjected to play their role as ligands. In recent times, researchers are working to find out some potential lead compounds from medicinal plants that are active against several enzymes and other proteins responsible for viral replication and growth ( Gupta et al, 2020b ; Krupanidhi et al, 2020 ; Pendyala and Patras, 2020 ). Several studies reported the inhibitory potential of several herb derived phytochemicals against SARS-CoV-2 ( Dhama et al, 2018 ; Gupta et al, 2020b ; Jalali et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, these phytochemicals can be useful for treating/managing neurological manifestation of COVID-19 by targeting the ACE2/spike proteins to suppress the penetration/attachment of SARS-CoV-2 to the CNS cells, what triggers the neurological signs ( Wu et al, 2020b ). Overall, evidence has shown berberine, thebaine, piperine (as alkaloids), withaferin A (steroidal lactone), nimbin, embelin, cafestol, murrayanine, murrayaquinone-A and andrographolide are phytochemicals with the potential antiviral effects for example through binding to spike protein in SARS-CoV-2, as well as ACE2 receptor ( Grover et al, 2011 ; Boukhatem and Setzer, 2020 ; Gupta et al, 2020 ; Parida et al, 2020 ). Consistent docking results showed the same acceptable inhibitory effects against SARS-CoV-2.…”
Section: Potential Of Phytochemicals Against Covid-19 Neurological Asmentioning
confidence: 99%
“…While drug repurposing towards targeting important proteins in SARS-CoV-2 are still under development, considerable volume of scientific evidence suggest that novel natural compounds with potential antiviral activities can be deployed against SARS-CoV-2 [ [11] , [12] , [13] ]. Studies have revealed that such compounds from indigenous herbs and medicinal plants may inhibit replication of coronaviruses, especially SARS-CoV-2 [ [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%